2011
DOI: 10.1097/inf.0b013e3182027c22
|View full text |Cite
|
Sign up to set email alerts
|

Improving Surveillance for Pediatric Clostridium difficile Infection

Abstract: These results demonstrate that the use of administrative data for CDI is a reliable and accurate method for identifying pediatric patients with CDI. The use of administrative data could facilitate the completion of larger studies due to its greater accessibility and reduced costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This definition of CDI has been previously validated in an inpatient setting with a positive predictive value of 83.0% and a negative predictive value of 99.9%. (13) HA-CDI was defined as CDI that occurred after at least 6 inpatient days.…”
Section: Methodsmentioning
confidence: 99%
“…This definition of CDI has been previously validated in an inpatient setting with a positive predictive value of 83.0% and a negative predictive value of 99.9%. (13) HA-CDI was defined as CDI that occurred after at least 6 inpatient days.…”
Section: Methodsmentioning
confidence: 99%
“…There is limited information on CDI colonization vs true infection, as the data are based on ICD-9 codes. Nevertheless, the ICD-9-CM code for CDI diagnosis has been validated in previous studies, and has been shown to correlate well with the results of C. difficile toxin assay [30, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…We screened for children with CDI using the International Classification of Diseases, Ninth Revision (ICD-9) code 008.45 (previously validated for CDI in hospitalized children 20 ) and/or positive test results for C difficile . We confirmed CDI by record review as having diarrhea (≥3 loose stools/day) and either a positive C difficile stool test (toxin assay or polymerase chain reaction [PCR] test, the latter used more routinely in study centers since 2011) or gross pseudomembranous colitis, per Society for Healthcare Epidemiology of America surveillance criteria.…”
Section: Methodsmentioning
confidence: 99%
“…This definition has greater specificity for CDI than using diagnostic codes or test results alone. 20 Cases of CDIAReA included in incidence calculations were confirmed by record review to be in the source population and have both CDI diagnosis code and positive test results. We examined trends in CDIAReA incidence using linear regression and adjusted for changes in CDI incidence.…”
Section: Methodsmentioning
confidence: 99%